TGF‐β inhibits IL‐7‐induced proliferation in memory but not naive human CD4+ T cells. Issue 2 (6th June 2017) - Nguyen, Thao P.; Sieg, Scott F.
Abstract : TGF‐ β differentially impairs IL‐7‐induced proliferation in memory and naiüve CD4+ T cells. Abstract : TGF‐β is a potent suppressor of T cell activation and expansion. Although the antiproliferative effects of TGF‐β are well characterized in TCR‐activated cells, the effects of TGF‐β on T cell proliferation driven by homeostatic cytokines, such as IL‐7, are poorly defined. In the current study, we found that TGF‐β inhibits IL‐7‐induced proliferation in memory, but not in naive human CD4 + T cells. TGF‐β impaired c‐myc induction in all CD4 + T cell maturation subsets, although the impairment was less sustained in naive CD4 + T cells. TGF‐β had no discernible effect on IL‐7R signaling (p‐STAT‐5, p‐Akt, or p‐S6) in memory T cells but selectively enhanced p‐S6 signaling in naive T cells. The inhibitory effects of TGF‐β on memory T cell proliferation were partially overcome by chemical inhibition of GSK‐3, which also led to enhanced c‐myc expression. These data suggest that TGF‐β could play an important role in limiting homeostatic proliferation of memory T cells. Our observations also point toward a novel strategy to subvert TGF‐β‐mediated inhibition of memory T cells by targeting GSK‐3 for inhibition.